"What Design Can't Do": the paradigm of disillusionment in the practice and teaching of Design (Revista de Ensino em Artes, Moda e Design, 2025)
This review examines the book “What Design Can't Do: Essays on Design and Disillusion” by Silvio Lorusso, an Italian designer and professor based in Portugal. The work proposes a new paradigm for theoretical production in Design, contrasting with many traditional canons that operate through a positive perspective. Lorusso explores disillusionment as an inherent condition of Design practice, education, and theory—not as something to be overcome but as a phenomenon to be acknowledged, documented, and organized.By addressing disillusionment, the author defines it as a collective sentiment that permeates the professional field, influencing its dynamics and exposing the limitations of an idealized discourse. Lorusso offers critical reflections to help understand this phenomenon, challenging the utopian expectations often imposed on Design and paving the way for a more nuanced and realistic view of the profession.